Growing young eaudiobook How friendship, optimism, and kindness can help you live to 100. - Zaraska, Marta (Appetite by Random House, 2020)
NATIONAL BESTSELLER A smart, research-driven case for why optimism, kindness, and strong social networks will help us live to 100. From the day her daughter was born, science journalist Marta Zaraska fretted about what she and her family were eating. She fasted, considered adopting the keto diet, and ran a half-marathon. She bought goji berries and chia seeds and ate organic food. But then her research brought her to read countless scientific papers and to interview dozens of experts in various fields of study, including molecular biochemistry, epidemiology and neuroscience. What Marta discovered shattered her long-held beliefs about aging and longevity. A strong support network of family and friends, she learned, lowers mortality risk by about 45 percent, while exercise only lowers it by about 23 percent. Volunteering your free time lowers it by 22 percent or so, while certain health fads like turmeric haven't been shown to help at all. These revelations led Marta Zaraska to a simple conclusion: In addition to healthy nutrition and physical activity, deepening friendships, practicing empathy and contemplating your purpose in life can improve your lifespan. Through eleven chapters that take her around the world, from catching wild mice in the woods of central England to flower arranging with octogenarians in Japan, from laboratories to "hugging centres," Marta embarks on an absorbing, entertaining and insightful journey to determine the habits that will have the greatest impact on our longevity. Deeply researched and expertly reported, Growing Young will dramatically change the way you seek a longer, happier life.